ANALISIS PENGARUH EVA (ECONOMIC VALUE ADDED) DAN MVA (MARKET VALUE ADDED) TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR SUBSEKTOR FARMASI DI BURSA EFEK INDONESIA - Novi Puspitasari; Halimatus Sa’diah; Susanti Prasetiyaningtiyas; Hari Sukarno (Study Program of Management Faculty of Economics and Business University of Jember, 2022)
Companies that are trying to enter the capital market aim to provide a general picture of the company, especially how the company is performing so that it can attract investors to invest their capital. Investors need measurement tools to inform the company's performance in order to get benefits or a profitable rate of return. This study aims to analyze the effect of Economic Value Added (EVA) and Market Value Added (MVA) on stock returns in pharmaceutical sub-sector companies. This research belongs to the type of quantitative research using a positivist paradigm. The population used is manufacturing companies in the pharmaceutical sub-sector with sampling using purposive sampling method to obtain samples that can represent the research criteria in order to obtain 8 companies that have met the specified criteria. The analytical method used is multiple linear regression analysis. From the results of the analysis, it is found that EVA (Economic Value Added) has no effect on stock returns, while MVA (Market Value Added) has an effect on stock returns of pharmaceutical manufacturing companies listed on the IDX for the 2015 – 2019 period.